Two siblings with Heimler syndrome caused by PEX1 variants: follow-up of ophthalmologic findings. (4th July 2021) - Herijgers, Dorien; Denayer, Ellen; Balikova, Irina; Witters, Peter; Jacob, Julie; Casteels, Ingele
ABSTRACT: Background: Heimler syndrome (OMIM number #234580 and #616617) is a rare condition comprising sensorineural hearing loss (SNHL), nail abnormalities and amelogenesis imperfecta. In addition, patients with this syndrome can have retinal dystrophies. Heimler syndrome is caused by bi-allelic pathogenic variants in the PEX1 or PEX6 gene. Only few patients with this syndrome have been reported. We hereby describe two siblings with genetically confirmed Heimler syndrome and provide imaging of the ocular phenotype. Materials and methods: The medical records of the siblings were reviewed retrospectively. Results: Both brother and sister were diagnosed with SNHL and amelogenesis imperfecta of the permanent teeth; one of the affected siblings also had nail abnormalities. Both patients presented to the ophthalmology department with suboptimal visual acuity, fundus abnormalities and intraretinal cystoid spaces. Full-field electroretinogram revealed a cone-rod dysfunction. A genetic analysis revealed a homozygous likely pathogenic variant c.3077 T > C (p.Leu1026Pro) in the PEX1 gene in both siblings. The parents are heterozygous carriers of the variant. Conclusion: We recommend performing regular ophthalmic examination in patients with Heimler syndrome since the ophthalmic manifestations can manifest later in life. Our patients presented with cone-rod dystrophy and intraretinal cystoid spaces. Review of the literature shows that the ocular phenotype can be very variable in patients with Heimler syndrome.